2015
DOI: 10.14737/journal.aavs/2015/3.8.430.434
|View full text |Cite
|
Sign up to set email alerts
|

First Pilot Study on the Prevalence of Tick Infestation in Livestock of Tehsil Hajira, Rawalakot, Azad Kashmir

Abstract: | Ticks (Acari: ixodid) are blood imbibing ecto-parasite of wide range of animals. Ticks and tick-borne infections impose major economic threats to the livestock industry throughout the world. The present study reports prevalence of tick in livestock population of Tehsil Hajira of District Rawalakot Azad Kashmir. Through random sampling technique, a total of 1350 animals were scrutinized for tick infestation in 6 villages with an average 225 animals per village from Tehsil Hajira, Rawalakot, Azad Kashmir. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
5
17
0
Order By: Relevance
“…Overall, H. anatolicum was the most abundant tick species found in this study, which agrees with previous studies from Pakistan [ 26 , 31 ] and bordering countries as well [ 32 , 33 ]. It parasitized all the animal species in both the agro-ecological zones.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, H. anatolicum was the most abundant tick species found in this study, which agrees with previous studies from Pakistan [ 26 , 31 ] and bordering countries as well [ 32 , 33 ]. It parasitized all the animal species in both the agro-ecological zones.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study revealed the highest prevalence of tick infestation in summer because in summer the weather was hot and humid which supported the survival of tick infestation. These results are at par with the results of Ghosh et al (2007), Shakoori (2009), Rony et al (2010), Sultana et al (2015) and Ali et al (2016) who also noted high infestation of ticks in Summer. However, the animals remained infested with ticks all over the year.…”
Section: Discussionsupporting
confidence: 82%
“…Detrimental effects of ticks to animals are loss of blood, irritation, stress and despair of the immune system. Due to the direct transmission of diseases into the host, ticks are highly responsible for economic losses in term of decreasing skin quality of cattle up to 20-30% (Sultana et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In our country, there were limited research reports concerning the prevalence of tick infestation found in domestic animals particularly in ruminants, and those studies were conducted in few agro-climatic regions [20-27]. A recent study conducted in two districts of lower Punjab indicates that the prevalence of bovine tick infestation (BTI) exceeds 50% [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The tick infestation is the most common and considered to be economically important in a domestic animal, and reported studies conducted in different species such as ruminants [ 11 ], sheep [ 12 - 15 ], goat [ 12 , 15 , 16 ], dairy cattle [ 15 - 18 ], and buffalo [ 16 - 19 ]. In our country, there were limited research reports concerning the prevalence of tick infestation found in domestic animals particularly in ruminants, and those studies were conducted in few agro-climatic regions [ 20 - 27 ]. A recent study conducted in two districts of lower Punjab indicates that the prevalence of bovine tick infestation (BTI) exceeds 50% [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%